2009
DOI: 10.2118/113656-pa
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Use of Kaolinite in Downhole Scale Management: Squeeze-Life Enhancement and Water Shutoff

Abstract: Summary Applied research has been undertaken to examine the potential of kaolinite combined with a kaolinite-fixation agent to increase squeeze lifetime through alteration of near-wellbore surface characteristics and mineralogy, and to provide water-shutoff control. With respect to enhancing squeeze lifetime, it is documented that kaolinite increases the quantity of inhibitor adsorbed. Conversely, clean sandstone with low clay content commonly provides a poor substrate for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Using high concentrations of inhibitor tends to produce self-associations in the bulk rather than adsorption on asphaltene, reducing their effectiveness [12,13]. More recently, attention has focused on increasing the effectiveness of inhibitors by increasing the adsorption of scale inhibitors on rock surface, hence increasing the lifetime of a squeeze treatment [14].These studies include: (i) mixing cations or Fe (II) ions with the scale inhibitor to provide better retention than using the inhibitor alone [15], (ii) adding pH modification chemicals to the inhibitor via a temperature dependent material such as urea, (iii) using mutual solvents (such as the small alkyl glycols) to change the rock wettability (more water wet) [16], and (iv) using kaolinite or other clay to enhance the inhibitor adsorption [17]. These studies, however, only showed limited reduction in the amount of inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Using high concentrations of inhibitor tends to produce self-associations in the bulk rather than adsorption on asphaltene, reducing their effectiveness [12,13]. More recently, attention has focused on increasing the effectiveness of inhibitors by increasing the adsorption of scale inhibitors on rock surface, hence increasing the lifetime of a squeeze treatment [14].These studies include: (i) mixing cations or Fe (II) ions with the scale inhibitor to provide better retention than using the inhibitor alone [15], (ii) adding pH modification chemicals to the inhibitor via a temperature dependent material such as urea, (iii) using mutual solvents (such as the small alkyl glycols) to change the rock wettability (more water wet) [16], and (iv) using kaolinite or other clay to enhance the inhibitor adsorption [17]. These studies, however, only showed limited reduction in the amount of inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Squeeze lifetimes, and extension of such, are important for improving scale management. There are some researches trying to prolong the lifetime of a squeeze treatment by cross-linking inhibitors (Bache and Nilsson, 2000), enhancing additive's precipitation and adsorption (Rabaioli and Lockhart, 1996) or applying kaolinite to modify near wellbore surface properties (Fleming et al, 2009).…”
Section: Scale Inhibitionmentioning
confidence: 99%